Correlation between health‐care costs and salivary tests. (17th May 2013) - Kakuta, Erika; Nomura, Yoshiaki; Naono, Yoshinobu; Koresawa, Keizo; Shimizu, Keita; Hanada, Nobuhiro
Abstract : The burden of health‐care costs relative to gross domestic product in Japan is increasing. A large percentage (7.6% in 2009) of the Japanese gross domestic product has been spent on health care, and this percentage has been increasing annually. Soaring health‐care costs have been recognised as a serious social problem. In this study, we attempted to estimate the relationship between periodontal disease and health‐care costs. Subjects consisted of teachers and staff members (35 men, 26 women; mean age, 45 ± 9 years) from two high schools. The salivary levels of lactate dehydrogenase and haemoglobin were adopted as biomarkers to assess periodontal disease. After salivary tests, data for the health‐care costs over the subsequent 6 months were provided by the mutual association of the public schools on an individual basis. Curve‐fit estimations were then performed where health‐care costs were used as a dependent variable and age or salivary levels of haemoglobin or lactate dehydrogenase were used as independent variables. However, no good fitness was obtained. Subsequently, multilayer perceptron neural networks were applied. With the neural networks, good fitness was obtained by using lactate dehydrogenase as an independent variable. The results of this study show that oral health, particularly periodontal disease, is correlated with total health‐care costs. The data presented in this study suggests that, from the perspective of both oral and systemic health, oral health can be a signpost in well‐being and health promotion.